Performance Evaluation in Hybrid and Dynamic Distributed Systems - Freitas, Allan Edgard Silva; Macêdo, Raimundo José de Araújo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2013: Anais do III Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2013)
Distributed systems can be characterized by processes that communicate with each other by message passing, through communication channels, and may be located at several computers spread over a communication network. These processes and communication channels are usually characterized by synchronous or asynchronous timeliness behavior, according to the characteristics of underlying system (operating system and communication sub-system). Unlike conventional systems, the timeliness characteristics of dynamic and hybrid distributed systems may vary over time, according to the availability of resources and occurrence of failures. Such systems are becoming common today because of the increasing diversity and heterogeneity of computer networks and associated devices. Due their high complexity, these systems are difficult to test or verify. In this paper, we introduce a simulation tool for such environments, where distinct fault models and timeliness properties can be dynamically assigned to processes and communication channels. Such a tool is meant not only for protocol evaluation but also for prototyping, allowing code reuse in real applications. Besides presenting the simulation tool, we show a few experiments that validate the simulator behavior.